The last voyage of Capt. Sir John Ross, R. N. to the Arctic regions; for the discovery of a north west passage; performed in the years 1829-30-31-32 and 33; to which is prefixed an abridgement of the former voyages of Captns. Ross, Parry & other celebrated navigators to the northern latitudes compiled from authentic information and original documents, transmitted by William Light, purser's steward to the expedition; illustrated by engravings from drawings taken on the spot - Huish, Robert, 1777-1850. (London : J. Saunders, 1835)
"On the position of the north magnetic pole. (Supplement)": 44 p. at end. Added t.-p., engr. Mode of access: Internet.